The Literature Review of Supply Chain Performance Measurement in the Manufacturing Industry - Kess, Pekka; Sillanpää, Ilkka (Polish Association for Production Management, 2012)
The article addresses the issues of Supply Chain (SC) performance measurement – the process of qualifying the efficiency and effectiveness of the supply chain. The aim of this study is to present a supply chain measurement approaches for manufacturing industry.The research is based on a review of the current understanding of supply chain management and literature related to supply chain performance measurement. This study creates a framework for supply chain measurement by presenting the main theory framework of supply chain performance measurement.It is stated that supply chain performance measurement is extremely important in developing supply chain. The measurement framework in this study offers guidelines for measuring the supply chain in manufacturing industry.
Keywords: supply chain; performance measurement; supply chain management; manufacturing industry; strategy; operations; fi=Johtaminen ja organisaatiot|en=Management and Organization|